Belgium : 2010 Article IV Consultation-Staff Report; Staff Supplement; and a Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2011)
After being hit by a severe recession in 2008-09, the Belgian economy is gradually recovering. When core inflation remained subdued in 2010, headline inflation jumped up due to the energy price hike. The growth of potential output is expected to revert to its declining trend over the medium term. Building upon the encouraging 2010 fiscal outcome, the caretaker government is preparing a draft federal budget for 2011. To reduce the overall deficit to 3 percent of GDP by 2012, significant additional tightening measures will be needed.